Analysis of Knowledge Level, Consumption Habits, Sugar and Calories Content in Ice Cream on the Nutritional Status of Depok Students: Analisis Tingkat Pengetahuan, Kebiasaan Konsumsi, dan Kandungan Gula serta Kalori pada Es Krim terhadap Status Gizi Mahasiswa Depok - Habieb, Salsabila Firdausiyah Nur; Ilmi, Ibnu Malkan Bakhrul; Nasrulloh, Nanang; Marjan, Avliya Quratul (Amerta Nutrition, 2024)
Background: Obesity is a nutritional problem in Indonesia. A factor that influences the incidence of obesity is a high-sugar diet (ex: ice cream products). The consumption rate of ice cream increases every year and is also accompanied by an increasing number of outlets providing ice cream products. Added sugar in ice cream contributes to an increased intake of high-calorie foods that leads to obesity. Objectives: To analyze level of knowledge, consumption habits, sugar and calorie content of ice cream on the nutritional status of Depok students. Methods: Observational research with cross-sectional design, analyzed with frequency distribution and chi-square test. Data were obtained using online questionnaire. The research was conducted in the city of Depok, involving 939 samples of Depok students selected with purposive sampling methods. Results: 667 (71.0%) students have a good level of nutritional knowledge and 578 (61.6%) students unusually eat ice cream. There is no relationship between the level of nutritional knowledge (p-value: 0.609) and ice cream consumption habits (p-value: 0.211) on the nutritional status of students. Vanilla ice cream cup with cookies and cream topping is the most preferred ice cream, containing 13.28 grams of sugar and 154.11 kcal calories. Conclusions: Depok students have good nutritional knowledge and unusually eat ice cream. The sugar and calorie content of the ice cream are high.